Socio-environmental accounting system in health management: a case study at the Vision Institute - Camasmie Abe, Tatiana; Miraglia, Simone (Sustainability in Debate, 2020)
In recent years, the society has increased the pressure on institutions to improve their social and environmental efforts, in addition to economic considerations in decision-making and internal behavior. This study analyzes the applicability of socio-environmental management tools in the health care sector through the partial application of the Environmental Management Accounting System called SICOGEA ”“ Generation 3. This is an investigative and descriptive case study conducted at the Vision Institute (São Paulo Institute of Studies and Research in Ophthalmology, Brazil), where information was collected through semi-structured interviews. The results demonstrated that the studied institution has a level of general sustainability of 22.4%, which is considered “Weak.” This means that although it conducts certain initiatives for environmental management, the institution may be causing damage to the environment.